Leiostyla L o v e, 1852 – Mollusca, Pulmonata – new fossils for the Neogene Sebia and Ukraine - Prysiazhniuk, V. A. (Reports of the National Academy of Sciences of Ukraine, 2015)
Representatives of genus Leiostyla L o v e have been firstly met in the Sarmatian deposits of Serbia (the well-known locality of mammals in Vrachevich) and in the middle Sarmatian of (the Volyno-Podoliya, the Letichev district). New species Leiostyla krstichae from Serbia and Leiostyla ex gr. gottschicki from Ukraine have been described.